MENINGKATKAN EFISIENSI WAKTU DAN SUMBERDAYA DALAM PROSES PENYUSUNAN PERENCANAAN PENDIDIKAN DENGAN PERENCANAAN BERBASIS DATA - Siti Rahmatullisa; Zainal Berlian; Baharudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Planning is at the heart of Islamic education development because it determines the direction, quality, and sustainability of educational institutions. However, in practice, the planning process is often time-consuming, resource-intensive, and poorly data-driven. This study aims to analyze the concept of Islamic education planning, the impact of time constraints and resource constraints on planning effectiveness, and the role and urgency of data in accelerating the planning process. The study used a qualitative approach with a literature review method. The results indicate that data-driven planning can improve time efficiency, resource optimization, and the quality of decision-making in Islamic education. Data and databases serve as an objective basis for needs analysis, priority setting, and ongoing evaluation. Thus, data-driven planning serves as a strategic instrument in realizing professional, transparent, and quality-oriented Islamic education governance.